Efektivitas Komite Audit dan Audit Internal terhadap Kasus Kecurangan dengan Whistleblowing System sebagai Variabel Pemoderasi - Utami, Luh; Handajani, Lilik; Hermanto, Hermanto (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
The study aims to examine the effect of the effectiveness of the audit committee   and internal audit on disclosure of fraud cases with a whistleblowing system as moderating. The research population of the company is listed on the Indonesia Stock Exchange in 2016-2017 and discloses whistleblowing system reporting. The sample was determined by purposive sampling obtained 102 samples. The data analysis tool is used Moderated Regression Analysis (MRA). The research   findings indicate a whistleblowing system strengthens the influence of audit and internal audit committees to uncover fraud cases. The implications of this research can be useful as a consideration for companies in making policies related to disclosure of whistleblowing systems. Keywords: Audit Committee, Internal Audit, Whistleblowing System, Fraud Cases